Brain-Derived Neurotrophic Factor Elevates Activating Transcription Factor 4 (ATF4) in Neurons and Promotes ATF4-Dependent Induction of Sesn2 - Liu, Jin; Amar, Fatou; Corona, Carlo; So, Raphaella W. L.; Andrews, Stuart J.; Nagy, Peter L.; Shelanski, Michael L.; Greene, Lloyd A. (Frontiers in Molecular Neuroscience, 2018)
Activating Transcription Factor 4 (ATF4) plays important physiologic roles in the brain including regulation of learning and memory as well as neuronal survival and death. Yet, outside of translational regulation by the eIF2-dependent stress response pathway, there is little information about how its levels are controlled in neurons. Here, we show that brain-derived neurotrophic factor (BDNF) promotes a rapid and sustained increase in neuronal ATF4 transcripts and protein levels. This increase is dependent on TrkB signaling, but independent of levels of phosphorylated eIF2. The elevation in ATF4 protein occurs both in nuclei and processes. Transcriptome analysis revealed that ATF4 mediates BDNF-promoted induction of Sesn2 which encodes Sestrin2, a protector against oxidative and genotoxic stresses and a mTor complex 1 inhibitor. In contrast, BDNF-elevated ATF4 did not affect expression of a number of other known ATF4 targets including several with pro-apoptotic activity. The capacity of BDNF to elevate neuronal ATF4 may thus represent a means to maintain this transcription factor at levels that provide neuroprotection and optimal brain function without risk of triggering neurodegeneration.